Էջեր հայկական ռոքի պատմութիւնից․ Մաս Գ. Հայկական ֆոլք -ռոքը որպէս ինքնութեան կրող - Խառատեան, Մանէ (տպ. Atlas)
This is the third part of a series of three research paper s which look at Armenian rock music. The third part highlights Armenian folk -rock bands and their music, which originated in the 20th century, during the Soviet era, and has reached new heights during the last 30 years. Folk songs inherited over the centuries undergo changes due to diverse factors. The patterns of these changes or modifications, which can be discerned, are common to all cultures of the world. Researchers who have studied these patterns, note that, similar to natural selection, where the strongest and most effective elements of biological diversity remain, likewise in music, strong rhythmic notes prevail over the centuries. The author notes that Armenian music, which was formed in the context of mythological ideas about pre-Christian, as well as Christian , life was also influenced by various historical events and developments, eventually taking the forms that we know today. The author argues that current Armenian folk -rock bands have glocalized rock music as they have incorporated its style and means into Armenian traditional and ethnograpic songs. This has not been a huge challenge for Armenian rock bands as most of the band members had received professional musical education. Among the several features of this glocalized rock music the author highlights the national logos the bands use, the national symbols, the national costumes, the stage decoration, and the national musical instruments they use. Besides, most of the playlist s of these Armenian folk -rock bands are composed of Armenian songs and lyrics. The author concludes that, in general, both in Armenia and the Diaspora, Armenian folk rock bears the influence of Armenian reality and culture.
Keywords: Հայկական ռոքի պատմութիւն